Implementasi Pendidikan Karakter Religius untuk Menumbuhkan Literasi Moral Siswa SD melalui Program Kampus Mengajar - Nasrudin, Ega; Fakhruddin, Agus (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research focuses on the character education process through the 7th batch of teaching campus programs conducted at SD Negeri 3 Nasol. The focus of this study is the process of implementing character education through the teaching campus program in elementary schools. Character education is carried out through habituation, integration, and imitation processes. This research is a descriptive qualitative research. Data was collected through interviews, observations, and documentation. The data analysis technique used is through the stages of data collection, data reduction, data presentation, and conclusion drawn. The results of this study show that there is a character education process carried out during the 7th batch of teaching campus assignments. Of course, the success of character education is inseparable from the role of assistance from the school which always helps in the implementation of the 7th batch of teaching campus work programs. The character education program in the habituation aspect that is carried out is the duha prayer together, reading asmaul husna before learning, and praying before and after learning. Meanwhile, the character education program in the integration aspect is carried out through fun learning activities, mini cinemas, and Ramadan Islamic boarding schools. The character education program activities in the imitation aspect are carried out through 5S habituation. These various activities succeeded in making students know about virtue values. Students are seen to be increasingly obedient to worship, disciplined, responsible, independent, and creative.